Correlation of MTHFR C677T Polymorphism with Male Infertility among Indian Population: Case-Control Study - Akash More; Namrata Anjankar; Jarul Shrivastava; Nancy Nair; Ritesh Jadhav (Wolters Kluwer Medknow Publications, 2024)
This case-control study investigated the correlation between male infertility in India and the methylenetetrahydrofolate reductase (MTHFR) C677T variant. Infertile males were utilized as the case group in the study, whereas fertile individuals served as the control group. The C677T polymorphism was genotyped using PCR-RFLP analysis (polymerase chain reaction-restriction fragment length polymorphism). The Chi-square test and odds ratio calculation were implemented in the statistical analysis method for assessing the correlation between the C677T mutation and infertility. The results of this study revealed that the case group (9.4%) had a substantially greater prevalence of the C677T variation than the control group (1.6%). The C677T variation is significantly associated with male infertility by the Chi-square test (P value: 0.006). According to these results, the MTHFR gene›s C677T variation may increase the incidence of male infertility in the Indian population. Additional evaluations were also conducted to investigate the association between the C677T variation and particular infertility indicators. The C677T variation has been demonstrated to have been significantly correlated with a low or missing sperm count (p 0.05). These findings highlight the potential function of the MTHFR gene in reproductive health and advance our understanding of the genetic underpinnings of male infertility. It is encouraged to investigate the underlying mechanisms and additional investigation of the underlying mechanisms and to support the creation of individualized approaches to diagnosing and managing male infertility.